MR Venography Using the 3D-MEDIC (Multi Echo Data Imaging Combination) Sequence for Lower Extremities - Saito, Ryo; Tomokazu, Shohji; Kitagawa, Hisashi; Noguchi, Keiji; Kishi, Takayuki; Sunohara, Nobuo (Japanese Journal of Radiological Technology, 2008)
It is possible to diagnose varicose vein from medical history and physical examinations including inspection and palpation. Non-contrast enhanced MRV (magnetic resonance venography) is becoming popular because it can be easily performed without being affected by the radiographer’s skill. We thought that the use of MEDIC (multi echo data imaging combination) would enable us to delineate varicose veins within a short acquisition time and without need for synchronization or contrast enhancement. We used the SIEMENS MAGNETOM Avanto 1.5-Tesla unit to acquire images. Our subjects were five healthy volunteers and five patients with varicose vein. The signal strength of deep veins and muscles were measured. The SNR (signal-to-nose ratio) of deep veins and the CNR (contrast-to-noise ratio) between deep veins and muscles were also measured. 1. a) flip angle, b) fat suppression methods, c) MTC (magnetic transfer contrast) pulse, and d) combined echo. Using the optimum image acquisition protocol following our preliminary study with varicose vein patients, the ability of the 3D-MEDIC method to delineate varicose veins was compared with that of the ECG-synchronized 2D-TOF method. We found that the following settings would enable us to acquire images from a wide range=coronal, within short acquisition time and needless ECG-triggering. 1. a) flip angle=20 degrees, b) fat suppression method=water excitation, c) MTC pulse=ON, d) combined echo=2. 3D-MEDIC was better than the 2D-TOF method in delineating the varicose vein itself and the connection between the varicose vein and deep veins. It is expected that 3D-MEDIC may be useful in the clinical diagnosis of varicose veins. (Article in Japanese)